(untitled) (Singaporean Journal of Business Economics and Management, 2013)
Despite the wide belief that the high social rates of returns to R&D investment justify government subsidy policy in advanced countries, there are only limited studies about whether government R&D subsidy affect corporate performance. This paper empirically examines the effect of government R&D subsidy on corporate performance using a unique data from the subsidy re-empowerment programme committee in Nigeria. The paper employs a regression and correlation analysis to determine the effect of government R&D subsidy on corporate performance using statistical package for social sciences (SPSS V.20). Our empirical results show that there is significant relationship between government R&D subsidies on corporate performance. These results suggest that government subsidies could help to overcome the barriers of R&D projects through sharing R&D failure risk with government and by reducing costs to undertake new technology development projects.